(untitled) (مجلة البحوث الأكاديمية, 2024)
Recurrent pregnancy loss (RPL) or Recurrent miscarriage (RM) can be defined as three or more consecutive pregnancy losses before 24 weeks of gestation. Many studies have proven that parental chromosomal abnormalities represent an important etiology of RM. This case of study was run to identify the role of chromosome rearrangement in RPL. To achieve the aim, a case of a phenotypically and normal physical examinations healthy couple, were subjected to cytogenetic analysis apparently after experiencing three RPLs. In their past the investigations were only limited to physical, imaging and routine laboratory testing in which no abnormal values were ever reported. Herein, the cytogenetic tests using G-banding showed that the wife was a carrier of pericentric inversion on chromosome 8; precisely 46,XX inv (8) (p11;q23), estimating the possible origin of the multiple pregnancy loss in this case. This finding underlies the importance of cytogenetic investigations in the routine management of RPL.